A common base answer to "Which country is most redistributive?" - Peter J. Lambert; Runa Nesbakken; Thor O. Thoresen (Statistics Norway, Research Department, 2015)
Which country is most redistributive? This question is often discussed in terms of comparisons of measures of redistribution when each country's tax schedule is applied to its pre-tax income distribution. However, we believe that what most authors have in mind when referring to the "most redistributive country" is one in which the tax schedule is unanimously most redistributive across all pre-tax income distributions. A stronger identification of the most redistributive tax schedule therefore implies applying each tax schedule to all pre-tax income distributions and compare redistribution for all possible combinations. Given that this is practically complicated, we suggest applying the transplant-and-compare method of Dardanoni and Lambert (2002), which provides a tax progressivity ordering of schedules according to a common base. This paper shows how the transplant-and-compare approach can be utilized to approach an identification of the most redistributive country. The method and its implications are discussed by employing micro data from Luxembourg Income Studies, also contrasting results to those obtained using standard measures of redistribution.
Keywords: H11; H23; 330; Redistributive effect; Personal income tax; Cross-country comparison; Common base